Dishing up Distinction: Language Materiality and Multimodal Coherence in Elite Foodways - Thurlow, Crispin; Haudenschild, Noëlle (Frontiers in Communication, 2022)
This paper arises as part of a discourse-focused commodity chain analysis of elite foodways in the international airline industry (Thurlow, 2020a). At the center of this critical intervention sits the business class airline meal as an epitomic manifestation of contemporary class privilege. As both a fraught social hieroglyphic and a complex semiotic assemblage, “premium” airline dining is articulated across different sites and through a range of different communicative practices and modes. With this in mind, we examine the language materiality of plateware (crockery), flatware (cutlery), glassware, and other tableware used for staging and promoting airline meal services. The specific object of our analysis is the transmodal interplay between words and things which helps generate both the cohesion and coherence of meals. This kind of textual unity and “inter-semiotic harmony” (Stöckl, 2014: 292) is key for the performative production of order which is, in turn, central to the classist production of distinction and (elite) status.